Defect processess after vacant possession at Block B Vertu Resort, Aspen Vision City, Batu Kawan, Pulau Pinang / Mohammad Asyraf Ikhwan Helmi - Helmi, Mohammad Asyraf Ikhwan (Universiti Teknologi MARA UiTM,Perak, 2022)
Aspen Group Sdn Bhd is a Penang-based company which diversify its business into 3 main categories which include development, healthcare, and food and beverage. In an ever-changing property development business, Aspen Group is also a real estate investment group established on the premise of delivering quality and affordability. Success, according to Aspen Group, derives from a consistent emphasis on innovation, creativity, and execution.